Cadmium sulphide-reduced graphene oxide-modified photoelectrode-based photoelectrochemical sensing platform for copper(II) ions - Ibrahim, I.; Lim, H. N.; Huang, N. M.; A., Pandikumar (Public Library of Science, 2016)
A photoelectrochemical (PEC) sensor with excellent sensitivity and detection toward copper (II) ions (Cu2+) was developed using a cadmium sulphide-reduced graphene oxide (CdS-rGO) nanocomposite on an indium tin oxide (ITO) surface, with triethanolamine (TEA) used as the sacrificial electron donor. The CdS nanoparticles were initially synthesized via the aerosol-assisted chemical vapor deposition (AACVD) method using cadmium acetate and thiourea as the precursors to Cd2+ and S2-, respectively. Graphene oxide (GO) was then dip-coated onto the CdS electrode and sintered under an argon gas flow (50 mL/min) for the reduction process. The nanostructured CdS was adhered securely to the ITO by a continuous network of rGO that also acted as an avenue to intensify the transfer of electrons from the conduction band of CdS. The photoelectrochemical results indicated that the ITO/CdS-rGO photoelectrode could facilitate broad UV-visible light absorption, which would lead to a higher and steady-state photocurrent response in the presence of TEA in 0.1 M KCl. The photocurrent decreased with an increase in the concentration of Cu2+ ions. The photoelectrode response for Cu2+ ion detection had a linear range of 0.5-120 μM, with a limit of detection (LoD) of 16 nM. The proposed PEC sensor displayed ultra-sensitivity and good selectivity toward Cu2+ ion detection.